vp100813_elic_NominalForms_predicative_possessive_past - Валентина Пуяковна Силкина (Надер); Олеся Ханина (Bernard Comrie, 2010)
O.Khanina collects with V.P.Nader predicative possessive endings in the past, on the example of niO 'child': nouns of sg. and pl. number, possessor of sg. and pl. number тундровый энецкий, русский Language_Name: Enets Language_Region: Asia Language_Country: Russia Project_Status: Complete Year: 2007 Start_Date: 2008-02-01 End_Date: 2011-01-31 Title vp100813_elic_NominalForms_predicative_possessive_past